Genetic diversity and population structure of sweet orange (Citrus sinensis) germplasm revealed by SSR and InDel markers - KUMAR, J PRASANTH TEJ; THIRUGNANAVEL, A; UPADHYAY, DEVENDRA Y; KAMDE, SNEHAL A; JALAMKAR, PRAFULLA R; MURKUTE, ASHUTOSH A (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2019–21 at ICAR-Central Citrus Research Institute, Nagpur, Maharashtra, in which two molecular markers, SSR and InDels were used to understand the genetic diversity and population structure of 72 sweet orange [Citrus sinensis (L.)] genotypes. The studied genotypes showed a genetic variability with an average genetic polymorphism of 68.89 and 56.52% with InDels and SSR, respectively. Allele numbers ranged from 1–2 with 1.86 and 1.25 average numbers of alleles per marker for InDel and SSR, respectively. Two dendrograms were constructed independently based on the InDels and SSR markers. In both cases, they formed 3 major clusters showing various degrees of variations concerning members of the clusters. Based on k-means clustering, the studied genotypes were divided into 2 distinct sub-populations. Soh Khylla, Soh Niairang, and Tasi, the genoptypes from north-eastern region exhibited informative and distinctive patterns in both the marker types.